Performance of Teak (Tectona grandis L.F) wood on exposure to outdoor weather conditions - DN Izekor; JA Fuwape (Journal of Applied Sciences and Environmental Management, 2011)
The performance of Teak wood on exposure to outdoor weather conditions was investigated. Six even age trees of similar class diameter comprising 15, 20 and 25- year old Teak wood respectively were studied. Wood samples were collected from three points along the tree radial and longitudinal positions. Percentage shrinkage of weathered Teak increased from the tree base to the top and also from the inner wood to the outer wood for the three age classes. It however decreased with increase in the age of the tree. The mean percentage shrinkage of weathered Teak obtained in the radial directions were 1.51, 1.30 and 0.73% while in the tangential directions, the mean value obtained were 3.14, 2.23 and 1.27% for ages 15, 20 and 25- year old Teak wood respectively. The results of the visual observation of the study samples showed that Teak wood on exposure to outdoor weather condition was resistant to surface splitting and checking in both radial and tangential directions. Discolouration and loss of brightness was observed for all the study samples on exposure to outdoor weather conditions irrespective of the tree age and the positions from where the wood sample was collected. Plantation grown Tectona grandis wood of older age classes in Edo State has higher resistance to shrinkage, surface splitting and checking. Its wood is therefore recommended for use as structural material in outdoor weather conditions @JASEM